Understanding The Productivity and Loyalty of Millennial Employees in The Hotel Business: Preliminary Evidence - Nenny Wahyuni; Suci Sandi Wachyuni; Kadek Wiweka; Shinta Teviningrum; Nicko Gana Saputra (Institute of Research and Community Outreach - Petra Christian University, 2024)
The company's ability to survive in a highly competitive environment relies heavily on employee productivity and loyalty. Contemporary millennial culture in the hotel industry is a topic of current societal discussion. Therefore, researchers have a keen interest in this area. The population for this study consists of all the employees belonging to the millennial generation working in the Front Office department of a 4-star hotel in Jakarta. The approach employs a combination of two distinct variables using both quantitative and qualitative methodologies. A total of 18 millennial employees from the front office department were surveyed, along with three interviewees consisting of the front office manager, assistant front office manager, and front office supervisor. Based on data collected through interviews, observations, and surveys, researchers have discovered that the millennial generation's front office department exhibits excellent employee productivity, characterised by a strong sense of enthusiasm and ambitious goals. However, the loyalty of the millennial generation towards their work is distinct. These employees frequently switch companies not due to a dislike for corporations, declining performance, or a poor work environment, but rather because they seek to gain extensive experience, build strong professional networks, and aspire to attain higher positions at a faster pace.